PENGARUH BAURAN PEMASARAN JASA TERHADAP LOYALITAS MAHASISWA STIE PERSADA BUNDA PEKANBARU - Susanti, Desi (Jurnal Tepak Manajemen Bisnis, 2016)
This study aims to determine the effect of mark eting mix on studentsâ loyalty at STIE PersadaBunda. STIE Persada Bunda as one of the universities in Riau is one of the choices for prospectivestudents from inside and outside Riau Province.It can be seen from the number of students is increasing every year. However, from two fieldsof study at STIE Persada Bunda, only Management field of study that has increased every year sincethe number of students of management within five (5) years always increase. If 2011 is the referencebase year in calculating the number of students, the growth of students has reached 83, 27% in 2015. Inthe contrary, the growth of students of Accounting from the year 2012 decreased by 2014. By 2015 thenumber of students began to increase, but still could not exceed the one in 2011.This research was conducted at STIE Persada Bunda Pekanbaru. The Population of thisresearch was the entire active students of STIE Persada Bunda in the academic year of 2015/2016.There were about 1,675 students, while the sample of this research was 95 students by using stratifiedrandom sampling. Analysis of the data used in this research were quantitative descriptive analysis andmultiple linear regression using SPSS 21.0 for windows . The result shows that marketing mix ofproduct, price, location, promotion, people, physical facilities and processes had affectedsimultaneously to studentsâ loyalty at STIE Persada Bunda .Promotional mark eting mix and the processdoes not affect the loyalty of students at STIE Persada Bunda partially, while the five other marketingmix of product, price, location, people, physical facilities partially affect the loyalty of students at STIEPersada Bunda